The Constitutional and Legal Organizing for The Caretaker Government in Iraq and Kurdistan Region - Ibrahim Mohammed Haje; Peshawa Khidher Rasul; Sakar Ameer Abdulkarim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This study deals with the concept of a caretaker government and an explanation of the constitutional, legal and administrative foundations upon which this government is based during the period of conducting daily business, and an explanation of the legal status of the caretaker government by addressing the cases of its realization and the scope of its constitutional and administrative powers in normal and exceptional circumstances, and the extent of the possibility of parliamentary oversight over it. Its actions or decisions, as well as the scope and effectiveness of judicial oversight over the actions and organizational or individual decisions of this government This study also addresses many of the constitutional loopholes that mar the texts of the Iraqi Constitution in force for the year (2005), and the texts of the regular legislation in force in Iraq and the Kurdistan Region of Iraq with regard to the concept of a caretaker government. Businesses and the limits of their powers and oversight over them with the aim of carrying out the necessary reforms in this regard Thisstudy also addresses many important decisions at the level of legislative, executive and judicial authority in thecomparative countries regarding the subject of the study, where they are analyzed and compared with each other and the necessary reforms in them are stated, especially in Iraq and the Kurdistan Region.